Peran Guru dalam Pembentukan Karakter Peserta Didik Sebagai Respon Terhadap Degradasi Moral - Karunia Hazyimara; Wenty Septria Dharma Suwarni; Fitri Indriani; Rosdiana (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The phenomenon of moral crisis that occurs in students really requires the role of teachers who are able to shape and foster the character of students. It takes teachers who are able to educate and direct students so that they have good character. The quality of teachers in Indonesia is improved through various trainings provided by the government and their respective schools. But with the current of globalization so strong, there is still a lot of moral degradation in the midst of students. The purpose of this study is to unravel the role of teachers in order to overcome moral degradation through character education. This research uses a method in the form of a qualitative approach to library research literature studies. The data collected is obtained through data identification by reading, understanding, discussing data, presenting and drawing conclusions sourced from relevant books and journals. The results of this study show that the concept of character education in Indonesia must be developed early and sustainably, seeing the phenomena and conditions that are found in Indonesia, showing that character education in schools is needed.